1997
DOI: 10.1111/1468-0289.00046
|View full text |Cite
|
Sign up to set email alerts
|

The Origins and Early Impact of the Minimum Wage in Agriculture

Abstract: This article examines the effects on wages and employment of the minimum wage in agriculture during the interwar period. It finds that the impact of regulation was to raise the wage for agricultural labourers by 13 per cent when it was (re)introduced in 1924, by 15 per cent in the late 1920s, and by more than 20 per cent in the 1930s. The effect on farm employment was to reduce it by about 54,000 (6.5 per cent) in 1929 up to a peak of 97,000 (13.3 per cent) in 1937. The minimum wage lifted out of poverty many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Similar to previous findings regarding the agricultural sector [42,43], this is likely due to significant differences between restaurants and agriculture: agricultural goods from geographically separate locations are substitutes to a much greater extent than restaurants over similar distances. While we cannot estimate the overall impact on DM employment due to the small sample size and the fact that this study is prospective, seven out of the 18 producers did indicate that they have already or will be reducing labor hours in the coming years.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to previous findings regarding the agricultural sector [42,43], this is likely due to significant differences between restaurants and agriculture: agricultural goods from geographically separate locations are substitutes to a much greater extent than restaurants over similar distances. While we cannot estimate the overall impact on DM employment due to the small sample size and the fact that this study is prospective, seven out of the 18 producers did indicate that they have already or will be reducing labor hours in the coming years.…”
Section: Discussionsupporting
confidence: 85%
“…Most of these studies focused on specific industries that employ low-wage workers, especially restaurants and hotels. In the agricultural sector, Gowers and Hatton [42] found that establishing a MW reduced poverty among farmworkers, and reduced farm employment. Moretti and Perloff [43] found that an increase in the federal MW increases the wage of hourly farmworkers, but not piece-rate workers.…”
Section: Impact Of Minimum Wage Changesmentioning
confidence: 99%
“…Subsequent work also finds increases in wages and decreases in employment in the farm sector [22][23][24]. Gilroy (1982) confirms this basic result using proprietary federal data on coverage [24].…”
Section: Minimum Wage and Us Agricultural Labor Marketsmentioning
confidence: 89%
“…These results are qualitatively similar to findings pertaining to the introduction of minimum wages in English and Welsh agriculture in 1917 (repealed in 1921 and reinstated in 1924). Gowers and Hatton (1997), for example, find that wage rates within agriculture increased substantially, while employment fell with reduced poverty to workers retaining their jobs [22].…”
Section: Minimum Wage and Us Agricultural Labor Marketsmentioning
confidence: 99%
“…Similar findings are reported for the effects of the non-agricultural British Wages Councils in the 1970s and 1980s by Dickens et al, (1994) and . The only other study of minimum wages in UK agriculture over the post-war period of which we are aware (Gowers and Hatton (1994) provide an analysis of the inter-war period), is by Lund et af. (1982).…”
Section: A Theoretical Framework For the Analysis Of The Effects Of Mmentioning
confidence: 99%